The 12-item Speech, Spatial and Qualities of Hearing Scale questionnaire: administration suggestions and guidance - Cañete, Oscar M. (Auditio, 2023)
Hearing questionnaires are extremely useful tools for describing people’s hearing abilities and for measuring and documenting hearing device fitting outcomes. The Speech, Spatial and Qualities of Hearing Scale (SSQ) questionnaire is often used and is even available in different versions and formats. However, detailed instructions and guidance for the clinician administering the questionnaire are limited. Below are some suggestions and guidance for reducing variability when administering the questionnaire, thereby maintaining consistency in both clinical and research settings alike.